Tanshinone I Inhibits IL-1β-Induced Apoptosis, Inflammation And Extracellular Matrix Degradation In Chondrocytes CHON-001 Cells And Attenuates Murine Osteoarthritis - Wang X; Fan J; Ding X; Sun Y; Cui Z; Liu W (Dove Medical Press, 2019)
Xipeng Wang,1 Jianbo Fan,2 Xiaomin Ding,2 Yuyu Sun,2 Zhiming Cui,2 Wei Liu2 1Department of Orthopaedic Surgery, The Central Hospital of Wuhan, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430010, People’s Republic of China; 2Department of Orthopaedic Surgery, The Second Affiliated Hospital of Nantong University, Nantong, Jiangsu 226001, People’s Republic of ChinaCorrespondence: Wei LiuDepartment of Orthopaedic Surgery, The Second Affiliated Hospital of Nantong University, Nantong, Jiangsu 226001, People’s Republic of ChinaEmail weiliu_111@126.comBackground: Osteoarthritis (OA) is a prevalent degenerative joint disease, which was characterized by inﬂammation and cartilage degradation. Accumulating evidence has demonstrated that Tanshinone I has an anti-inflammatory effect in various diseases. However, the efficacy of Tanshinone I as an anti-inflammatory agent in OA remains unclear. This study aimed to explore the role of Tanshinone I on OA both in vitro and in vivo.Methods: CHON-001 cells were treated with IL-1β (10 ng/mL) for 72 hrs to induce OA model in vitro. Meanwhile, CHON-001 cells were pre-treated with 20 μM Tanshinone I for 24 hrs and then stimulated with IL-1β (10 ng/mL) for 72 hrs. CCK-8, immunofluorescence and flow cytometry assays were used to detect the viability, proliferation and apoptosis in CHON-001 cells, respectively. Western blotting assay was used to detect the levels of collagen II, aggrecan, MMP-13, cleaved caspase 1, Gasdermin D, SOX11 and p-NF-κB in CHON-001 cells. In addition, the mouse model of OA was built by anterior cruciate ligament transection (ACLT) in the right knee. Meanwhile, the mice were administrated with 10 or 30 mg/kg Tanshinone I for 8 weeks. Safranin-O/Fast Green staining was used to assess cartilage destruction in a mouse model of OA.Results: In this study, IL-1β significantly induced apoptosis, extracellular matrix degradation and inflammatory response in CHON-001 cells. Tanshinone I significantly inhibited IL-1β-induced apoptosis in CHON-001 cells. In addition, the IL-1β-induced collagen II, aggrecan degradation, SOX11 downregulation, and MMP-13 and p-NF-κB upregulation in CHON-001 cells were notably reversed by Tanshinone I treatment. Moreover, Tanshinone I alleviated cartilage destruction and synovitis and reduced OARSI scores and subchondral bone thickness in a mouse model of OA.Conclusion: Our findings showed that Tanshinone I could alleviate the progression of OA in vitro and in vivo. These results demonstrated that Tanshinone I might be regarded as a promising therapeutic agent for the treatment of OA.Keywords: osteoarthritis, IL-1β, Tanshinone I, chondrocytes